TAFSIR FUNDAMENTALIS: Tafsir Kontemporer Sarat Bias Ideologis - Ummu Sa'adah (Fakultas Syariah - IAI Al-Qolam Malang, 2021)
Fundamentalism ideology is the massive challenge towards systematical structures including structural state and government, educational aspect, economy, social and cultural aspects. By using systematic approach on al-Qur’an and Hadits interpretations based on Islamic ideology, fundamentalism claims to build their own world perspectives. Their perspectives commonly construct prosecute separations among Islamic society from humanities aspects while claimed that their ideology is universal. This concern need to be wisely determined in which the fundamentalism ideology appear in complex society such as Indonesia. The impacts within society is a certain concern. Thus, we should have any consideration to live in plural and complex society. This is the main course of our concern to compose Islamic ideas of rahmatal lil alamin.